Multiwavelength JWST Observations of (3200) Phaethon Show a Dehydrated Object with an Aqueously Altered Origin - Cristina A. Thomas; Andrew S. Rivkin; Ian Wong; Matthew M. Knight; Sean E. Marshall; Christopher W. Haberle; Aidan Madden-Watson; Joshua P. Emery; Annika Gustafsson; Stefanie N. Milam; Heidi B. Hammel; Ellen S. Howell; et al. (The Planetary Science Journal)
We present JWST observations of the near-Earth asteroid (3200) Phaethon using NIRCam, NIRSpec, and MIRI to further investigate the composition of Phaethon’s surface. Our NIRSpec data confirms that Phaethon’s surface is dehydrated, showing no evidence of hydrated minerals in the 3 μ m region. We estimate an upper limit on the hydrogen content in phyllosilicates of 0.06 wt%. Comparisons with laboratory spectra of carbonaceous chondrites suggest that Phaethon’s surface composition is best matched by thermally metamorphosed samples of the CM chondrite Murchison (heated to 1000 °C), rather than CY meteorites as previous work suggested. We find no evidence of ongoing surface evolution due to recent perihelion passages. A comparison of the mid-infrared spectra of Phaethon and Bennu shows distinct spectral differences that are consistent with their different thermal histories. Our findings further refine our understanding of Phaethon’s current surface composition and evolution and provide additional insights for the upcoming DESTINY ^+ mission.